The Routledge companion to nonprofit management - Anheier, Helmut K.; Toepler, Stefan (Routledge companions in business, management and accounting, 2020)
Inhalt: chapter 1 Nonprofit Management Introduction and overview / With Stefan Toepler, Helmut K. Anheier -- Part I Management context -- chapter 2 A Changing Management Context The US, UK, Canada and Australia / With Susan D. Phillips -- chapter 3 Nonprofit Management Context Continental Europe and Scandinavia / With Georg von Schnurbein, Alice Hengevoss -- chapter 4 Nonprofit Management Context Central and Eastern Europe / With Peter Vandor, Clara Moder, Michaela Neumayr -- chapter 5 Nonprofit Management Context Russia and the FSU / With Lev Jakobson, Irina Mersianova, Natalya Ivanova -- chapter 6 Nonprofit Management in Asia / With Tamaki Onishi, Naoto Yamauchi -- chapter 7 Nonprofit Management Context The Middle East and North Africa / With Omar Bortolazzi -- chapter 8 Nonprofit Management Context Africa / With Jacob Mwathi Mati -- chapter 9 The Latin American Context The challenge of managing advocacy and impact inclusion / With Urs Jäger, Felipe Symmes, Rober Gutiérrez -- part Part II Leading and planning -- chapter 10 Composition of Nonprofit Boards Summary of factors that account for who governs nonprofits/ With William A. Brown -- chapter 11 Leadership / With Ruth Simsa -- chapter 12 Beyond Codes Values, virtues, and nonprofit ethics / With Ki Joo Choi, Roseanne Mirabella